Radicalization as a Functional Aspect of Crime - Kombo, Paul (Mediterranean Journal of Social Sciences, 2017)
Radicalization into extremism and terrorism is a controversial topic amongst scholars on the approaches used to understand the phenomenon. This paper examine some theories on the subject and the debate raging amongst scholars with regard to the differing models and approaches. The key theories examined in respect to radicalization include the theological model, the psychological approach, vulnerability explanations, discrimination/alienation models and political explanations.
Keywords: Security; Crime; Radicalization